Deviant behaviors and procedural justice: Mediating role of perceived organizational support - Nasib Dar; Wali Rahman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The purpose of this study is to empirically examine the relationship between procedural justice and deviant workplace behavior with the mediation of perceived organizational support. After applying purposive sampling technique, a sample of 150 respondents has been drawn from the target population. Data on the three variables with the help of a single adopted questionnaire have been collected. Data has been analyzed through correlation and regression analysis. Results revealed that: 1) procedural justice and deviant workplace behavior has negative and significant relationship; 2) procedural justice has significant and positive relationships with perceived organizational support; 3) deviant workplace behavior has a significant and negative relationship with perceived organizational support; and 4) the perceived organizational support acts as a partial mediator between procedural justice and workplace deviance. The results have implications for managers in the sense that if they have policies based on justice and are successful in the dispensation of procedural justice, perpetration of negative behaviors of workforce could be minimized, if not eliminated. Besides, this will boost the morale of employees and they will contribute positively to achieve the organizational goals. The study has included perceived organizational support as a mediator for the first time.
Keywords: 330; procedural justice; perceived organizational support; interpersonal deviance; organizational deviance